A Synergy Model for Sustainable Tourism and the Blue Economy in the Coastal Area of East Lombok Regency - Kamariani, Baiq Dewi; Eka Asbarini, Nur Fitri; Bahri, Salmi Yuniar (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to formulate a synergy model between sustainable tourism and the blue economy in the coastal areas of East Lombok Regency. The background of this research is based on the great potential of coastal areas that are rich in marine resources but still face environmental degradation, low community welfare, and the suboptimal utilization of marine potential. The research method uses a descriptive qualitative approach with data collection techniques through literature studies, field observations, and interviews with stakeholders, including local government, tourism actors, coastal communities, and academics. Data were analyzed by adapting the Indonesian Ocean Health Index (IKLI) and Ocean Health Index (OHI), as well as SWOT analysis to identify opportunities, challenges, strengths, and weaknesses in the development of blue economy-based tourism. The results show that East Lombok coastal tourism has great potential through marine tourism, ecotourism, fisheries, and salt farming. However, the implementation of the blue economy concept is still not optimal due to limited infrastructure, institutional capacity, and coordination among stakeholders. The proposed synergy model emphasizes integration between environmental conservation, local community empowerment, and sustainable policy support. This research contributes to strengthening the literature on coastal development and serves as a reference for sustainable tourism policy development in East Lombok.